Designing Animations and Simulations for Ohm's Law - Nigmet Koklu; Dundar Yener; Hamdi Sukur Kilic (International Journal of Applied Methods in Electronics and Computers, 2016)
Rapid developments in technology,  diversification of tools provided that can be used in the education stage. These new technologies facilitate learning improving the quality of learning and affects students' performance.  In accordance with physics laws, it is desired to describe events or experiments. It is possible to create animations and simulations with the help of various programs in the computer.  It is thought that via animation and simulation, student can learn the concepts which can be learned in laboratories used for physics lessons with lower cost and in shorter time.  In this study, general physics course and laboratory test commissioned by the resistance ammeter-voltmeter method of determination of the issue are utilized in better animation lectures and simulations in order to comprehend by the students.  Descriptions relating to experiments and issues were formed as animations.  With animations, it has been shown how ammeters, voltmeter and rheostat will be connected, to the circuit.  With the sample in the animations, it has been shown that the extraction of the formula how to calculate the current and voltage values from ammeter and voltmeter.  In the simulation which is given at the end of the experiment, let the student to enter to the blank space in the table which the values students want to enter, it is aimed for students to understood and test how good they can understand the fact that how potential difference, flow violence or resistance values are calculated.  It has also been worked to defeat misconceptions on this issue. In this way, more comfortable experiment understanding of the students' has been targeted.